2015
DOI: 10.1074/mcp.m114.039370
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals Dynamic Interaction of c-Jun N-terminal Kinase (JNK) with RNA Transport Granule Proteins Splicing Factor Proline- and Glutamine-rich (Sfpq) and Non-POU Domain-containing Octamer-binding Protein (Nono) during Neuronal Differentiation

Abstract: The c-Jun N-terminal kinase (JNK) is an important mediator of physiological and pathophysiological processes in the central nervous system. Importantly, JNK not only is involved in neuronal cell death, but also plays a significant role in neuronal differentiation and regeneration. For example, nerve growth factor induces JNK-dependent neuronal differentiation in several model systems. The mechanism by which JNK mediates neuronal differentiation is not well understood. Here, we employed a proteomic strategy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…In total, 20 ml of denaturation buffer were added to 10 ml of protein samples and used for in-solution protein digestion as described previously [27]. Briefly, proteins, solubilized in denaturation buffer, were reduced with 10 mM DTT for 30 min, followed by alkylation with 55 mM iodoacetamide for 20 min, and overnight digestion with 1 mg lysyl endopeptidase (LysC) (catalogue number 125-05061, Wako, Japan), resuspended in 50 mM ammonium bicarbonate (ABC).…”
Section: (D) Protein Extractionmentioning
confidence: 99%
“…In total, 20 ml of denaturation buffer were added to 10 ml of protein samples and used for in-solution protein digestion as described previously [27]. Briefly, proteins, solubilized in denaturation buffer, were reduced with 10 mM DTT for 30 min, followed by alkylation with 55 mM iodoacetamide for 20 min, and overnight digestion with 1 mg lysyl endopeptidase (LysC) (catalogue number 125-05061, Wako, Japan), resuspended in 50 mM ammonium bicarbonate (ABC).…”
Section: (D) Protein Extractionmentioning
confidence: 99%
“…However, while Cdk2 does phosphorylate PSF in cells and in vitro , a version of PSF containing T687 as the only putative Cdk2 site is not a substrate for phosphorylation by this kinase . Two additional serine/threonine kinases, protein kinase C α (PKCa) and the c‐Jun N‐terminal kinase (JNK), have been shown to associate with PSF, although it remains to be determined if PSF is a substrate for the activity of these kinases, and if so, which residues are phosphorylated …”
Section: Regulation Of Psfmentioning
confidence: 99%
“…These results indicated that SFPQ functions in the cytosol as well as the nucleus. Western blot analyses showed that NONO and SFPQ were colocalized in the cytosolic and nuclear fractions, but more amount was shown in the nucleus than in the cytosol (Sury et al, 2015). The evaluation of proximity ligation assay signals with NONO antibody, SFPQ antibody, and 4',6-diamidino-2-phenylendole (DAPI) nuclear counterstaining also revealed that NONO-SFPQ colocalization was mainly found in the nucleus.…”
Section: Sfpqmentioning
confidence: 99%
“…Therefore, they suggested that the coiled coil interaction and polymerization domains of SFPQ are necessary for the localization in paraspeckles (Lee et al, 2015). The coiled coil structure was visualized using negative stain electron microscopy (Lee et al, 2015), and the location was investigated using confocal microscopy (Sury et al, 2015). SFPQ was accumulated in the dark nucleolar caps.…”
Section: Sfpqmentioning
confidence: 99%
See 1 more Smart Citation